Fiscal management and political budget cycles in transition economies: data panel analysis - Radonjić, Ljubivoje; Despotovic, Danijela Z; Cvetanovic, Slobodan (Serbian Journal of Management, 2020)
In this paper, on the basis of relevant statistical tests, the influence of the electoral process on the trajectory of fiscal indicators in the transition countries is analyzed. The aim of the research is to identify the political manipulation of certain fiscal policy mechanisms in transition countries.The focus of the survey is on the growth of general government spending, the reduction of general government revenues and the creation of budget deficits as the coherent consequences of fiscal expansion in the pre-election period. By testing, there is no relevant evidence of the use of tax incentives as a form of political action on the economic sphere. On the other hand, the results of the survey indicate that in the observed countries, there really is a rise in government spending in the period before the election process and, consequently, the growth of budget deficits. However, according to the same findings, in the post-election period there is no reduction in consumption. Growth in general governments consumption continues, but to a lesser degree, which in turn leads to the correction of the budgetary balance.
Keywords: political budget cycles; fiscal policy; electoral process; transition economies